Middle Persian Graffiti on Sāsānian and Arab-Sāsānian Coins at the American Numismatic Society - Daryaee, Touraj (Anabasis. Studia Classica et Orientalia, 2017)
This essay is a study of fifteen graffiti on Sasanian and Arab-Sasanian coins from the American Numismatic Society in New York. The markings are mainly concerned with the quality of the coin, as well numbers and other markings. The graffiti are mainly from the time of Xusrō II to the early Islamic period when there were political upheavals.